Post-cracking behaviour of steel fibre reinforced concrete - Barros, Joaquim A. O. (2005)
Recently, RILEM TC 162-TDF has proposed equivalent, feq, and residual, fR, flexural tensile strength parameters to characterize and simulate the post-cracking behaviour of steel fibre reinforced concrete (SFRC) structures. In the current work, more than two hundred flexural tests are carried out according to the RILEM TC 162-TDF recommendations and the corresponding values of feq and fR parameters are evaluated. In series of specimens reinforced with fibres of a distinct length/diameter ratio, similar values of feq and fR parameters were obtained in these series. Although a strong correlation between feq and fR was determined, a larger scatter of fR values was observed thereby revealing feq to be more appropriate for design purposes. A numerical strategy involving a cross sectional layered model and an inverse analysis was developed to evaluate the post-cracking stress-strain and the stress-crack opening diagrams for the tested SFRC. This strategy was also used to determine a relation between the post-cracking strain, Epcr, and the crack opening displacement, w, (Epcr= w/Lp) which is useful for evaluating the crack opening when numerical strategies based on a stress-strain approach are used. The obtained Lp values range from half the specimen cross section height to half the distance between the tip of the notch and the top of the cross section.